Penerapan Gaya Desain Modern Natural pada Perancangan Interior Museum Teh di Surabaya - Andrie Wardhana Lokito; Sriti Mayang Sari (Intra, 2013)
Indonesia is one of the largest tea producer in the world. However, Indonesia doesn’t have a place to give an information about the tea plants especially in Surabaya. The lack of interest of the people of Surabaya to go to the museum is also a problem due to the museums in Surabaya are less attractive and the people in Surabaya prefer to spend their leisure time at the mall. Interior design of a tea museum in Surabaya aims to provide a place for introducing tea plants as well as becoming one of the recreational place based in education to the people of Surabaya. Interior design of the tea museum has a different design style from the other museums in Surabaya, that is with the application of modern natural design style, also being the only museum in Indonesia, which is located in the mall